2016
DOI: 10.1093/annonc/mdw155
|View full text |Cite
|
Sign up to set email alerts
|

CNS infections in patients with hematological disorders (including allogeneic stem-cell transplantation)—Guidelines of the Infectious Diseases Working Party (AGIHO) of the German Society of Hematology and Medical Oncology (DGHO)

Abstract: Diagnosis of CNS infections remains a great challenge in patients with hematological disorders since symptoms might both be masked and be mimicked by other conditions such as metabolic disturbances or consequences from antineoplastic treatment. Thus, awareness of this complication is crucial and any suspicion of a CNS infection should lead to timely and adequate diagnostics and treatment to improve the outcome in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 269 publications
(345 reference statements)
3
58
0
6
Order By: Relevance
“…On the other hand, we found that β‐D‐Glucan has only been occasionally determined on CSF, although this is a very recent epidemiologic study. This indirect diagnostic test on the CSF should, therefore, be useful, also in accordance with recent literature results …”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…On the other hand, we found that β‐D‐Glucan has only been occasionally determined on CSF, although this is a very recent epidemiologic study. This indirect diagnostic test on the CSF should, therefore, be useful, also in accordance with recent literature results …”
Section: Discussionsupporting
confidence: 86%
“…Therefore, in patients with pulmonary mycosis, the persistence of fever, despite a pulmonary improvement, or the onset of a headache or other neurological signs, such as diplopia, should never be underestimated. With regard to the diagnosis of IFIs, our data show that indirect methods of diagnosis are now commonly used including radiological examinations and biological markers such as GM, which represents a well consolidated diagnostic method . β‐D‐Glucan appears not to be widely used, both for blood and CSF.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations